Linearly polarized emission from self-assembled microstructures of mesogenic polythiophenes - Ananthakrishnan, Soundaram Jeevarathinam; Wadgaonkar, Prakash P.; Somanathan, Narayanasastri (Physical Chemistry Chemical Physics, 2014)
This work reports on linearly polarized photoluminescence and electroluminescence through spontaneous self-assembly of mesogenic polythiophenes under ambient conditions. A systematic structural variation and different alkyl chain lengths lead to three series of closely related mesogenic polythiophenes viz.; TPn, TNn and TVn. Polarized light emitting diodes fabricated from TV12 by solution processing with the configuration of ITO/PEDOT:PSS/Polymer/Al show linearly polarized electroluminescence with a dichroic ratio of 14.32. Spun thin films of TV12 elicited a dichroic ratio of 15.02 in photoluminescence. Studies using a range of techniques such as; atomic force microscopy, grazing incidence X-ray diffraction, fluorescence anisotropy, linear dichroism, fluorescence lifetime and dynamic light scattering reveal that the presence of highly ordered self-assembly was responsible for the dimensional confinement of optoelectronic properties. The ordering in the thin films originates from vinyl groups in the side chains of the TV12 polymer. Further studies on device characteristics show higher charge carrier mobility in polymers with vinyl side chains. Solution processed PLEDs show a maximum brightness of 863 cd m(-2) for the TP12 polymer and TV12 based LEDs show a maximum brightness of 524 cd m(-2).